3D Bioprinting: 3D Bioprinting of Developmentally Inspired Templates for Whole Bone Organ Engineering (Adv. Healthcare Mater. 18/2016). Issue 18 (21st September 2016) - Daly, Andrew C.; Cunniffe, Gráinne M.; Sathy, Binulal N.; Jeon, Oju; Alsberg, Eben; Kelly, Daniel J.
Abstract : A novel biofabrication strategy is described by Daniel R. Kelly and co‐workers. On page 2353, 3D bioprinting is used to engineer the developmental precursor to an adult organ. These bioprinted cartilage templates have the capacity to mature into vascularized bone organs in vivo. It is possible to reinforce these immature cartilage precursors with poly‐caprolactone microfibres, providing a level of mechanical functionality compatible with implanting such immature organ rudiments into load bearing locations in vivo.